Genetic Characterization of Echinococcus granulosus sensu stricto from Ruminants in Greece. Comparison with Findings in Türkiye and Reports from the Balkans and Mediterranean Countries - Roinioti, Erifylli; Bossis, Ioannis; Simsek, Sami (Springer Int Publ Ag, 2025)
Purpose Cystic Echinococcosis (CE) is endemic in ruminants in Greece. The aim of this study was to investigate the genetic variability of Echinococcus granulosus sensu stricto (E. granulosus s.s.) in carcasses of ruminants in the country and to compare the results with findings in neighbouring T & uuml;rkiye. The geographic distribution of the domestic haplotypes in the Balkans and Mediterranean countries was assessed. Secondary findings regarding the species and the age of the intermediate host in Greece are also discussed. Methods A total of 131 CE cysts of E. granulosus s.s., isolated from an equal number of carcasses of ruminants at slaughterhouses within Greece and a provincial slaughterhouse in T & uuml;rkiye, represented the data matrix of the study. Total genomic DNA was isolated from the germinal layer of the CE cysts and PCR was performed targeting fragments of cytochrome c oxidase subunit 1 (CO1) and nicotinamide dehydrogenase subunit 1 (NADH1) mitochondrial genes, followed by sequencing. The results were analyzed both independently (CO1, NADH1) and combined (CO1 + NADH1). Results/Conclusion The two countries shared six haplotypes of E. granulosus s.s. genotype G1. The presence of a dominant, common in both countries, haplotype was observed. E. granulosus s.s. genotype G3 was detected in both countries, however, different haplotypes were identified. Unique (not previously described elsewhere) haplotypes of E. granulosus s.s. were found in both countries (11 haplotypes in Greece, two haplotypes in T & uuml;rkiye). Overall, 11 haplotypes identified in carcasses in Greece have been reported in a wide range of hosts, including humans, in the Balkans, the Mediterranean countries or in Greece (in earlier studies).
Keywords: E. granulosus s.s.; Mitochondrial genes; Haplotype network; Ruminants; Greece; T & uuml;rkiye